Farmers' Participation in Messenger-Based Social Groups And Its Effects on Performance in Irrigated Areas of Kazakhstan and Uzbekistan - Kurbanov, Zafar; Tadjiev, Abdusame; Djanibekov, Nodir; Govind, Ajit; Akramkhanov, Akmal (Wiley, 2024)
he penetration of information and communication technologies (ICTs) in farming communities is increasing the use of smartphone-based instant messaging apps. Despite this, the reasons behind participation and the impact on farm productivity in developing countries remain unexplored. This study uses survey data of cotton growers in Kazakhstan and Uzbekistan to explore factors explaining participation in social media groups and its impact on farm performance. The results show that the factors and benefits differ across these two countries. Participation in social media groups has a positive effect on cotton yields in both countries, but increases revenue only in Kazakhstan. We discuss possible reasons for contrasting results and policy implications for improving agricultural extension and advisory services in Central Asia. Scaling up smartphone-based e-extension should focus on younger, more educated farmers. Emphasizing associated economic benefits and fostering decision-making autonomy among farmers will be crucial for creating conducive environment for benefiting from e-extension services.